Relationship Between Vascular Endothelial Growth Factor and Severity of Hepatocellular Carcinoma - Arles - -; Rino Alvani Gani; Ari Fahrial Syam; Hamzah Shatri (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2015)
Background: Severity of hepatocellular carcinoma (HCC) that is assessed using Barcelona Clinic Liver Cancer (BCLC) classification is a main prognostic factor of hepatocellular carcinoma. Assessment of the serum level of Vascular Endothelial Growth Factor (VEGF) is considered to reflect the severity of HCC. However, there is still no fundamental basis of the association of severity of HCC with the serum VEGF level. The objective of this study is to know the relationship between serum VEGF levels with the severity of HCC by assessing the average difference of serum VEGF level in various severity of HCC.Method: This study was a cross sectional study to identify the association between serum VEGF levels with the severity of HCC based on BCLC classification. This study was performed in Cipto Mangunkusumo Hospital between January and May 2015. Statistical tests used to evaluate the association between serum VEGF level with BCLC classification was one-way ANOVA analysis, and continued with post hoc Tukey Schaffe analysis.Results: A total of 61 subjects with HCC were included into this study. In this study, we did not find subjects with stage 0 BCLC. The average of serum VEGF level in stage A BCLC was 288.26 ± 156.6 pg/mL; stage B BCLC: 434 ± 164.8 pg/mL; stage C BCLC: 785.57 ± 194.25 pg/mL; stage D BCLC: 1537.97 ± 660.62 pg/mL. One-way ANOVA analysis showed significant difference (P 0.001) between serum VEGF level and HCC severity based on BCLC classification. Post hoc Tukey Schaffe analysis showed the presence of significant difference between stage A and C BCLC (p 0.05) and stage A and D BCLC (p 0.001), stage B and D BCLC (p 0.001), and stage C and D BCLC (p 0.001). There was no significant difference between stage A and B BCLC, and between stage B and C BCLC.Conclusion: It was found that serum VEGF level increased in accordance to the HCC severity based on BCLC classification, particularly for stage B BCLC and above.